The big three in economics Adam Smith, Karl Marx, and John Maynard Keynes - Skousen, Mark (Gale virtual reference library, 2007)
Traces the turbulent lives and battle of ideas of the three most influential economists in world history: Adam Smith, representing laissez faire; Karl Marx, reflecting the radical socialist model; and John Maynard Keynes, symbolizing big government and the welfare state.